An initial investigation in the viability of degraded modes for advanced RF seekers - Simpore, Ulrich B. Y.; Telescu, Mihai; Wickramasinghe, Thusitha; Balleri, Alessio; Deza, Julien; Bodrogi, Melinda; Tanguy, Noël (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Existing air-to-air RF seekers do not feature a specified degraded mode. The existence of such a mode would greatly increase the resilience of the radar seeker, reducing the chances to see a mission compromised by either technical failure or deliberate impairment (countermeasures). However, the problem is extremely challenging due to timing aspects as the mission is extremely short. This paper presents an initial investigation and the results of an initial study to identify, on receive only, the array components most likely to cause faults, to find solutions for increasing resilience and to establish the most promising pathways to reconfiguration. It is an ambitious first step on a technical challenge never investigated before.
Keywords: 40 Engineering; 33 Built Environment and Design; 4001 Aerospace Engineering; 11 Sustainable Cities and Communities